Manipulation of the ACC (1-aminocyclopropane-1-carboxylic acid) deaminase gene in Verticillium dahliae reveals a binary role for ACC in regulating virulence and plant defense: Two sides of the same coin - Tsolakidou, Maria Dimitra (Department of Agricultural Sciences, Biotechnology and Food Science, Faculty of Geotechnical Sciences and Environmental Management, Cyprus University of Technology, 2019)
The maintenance of high agricultural productivity as response to an increasing global demand for food and the exploitation of natural resources have become major challenges in both developed and developing countries. In addition, it is a persistent issue worldwide that a large number of plant pathogens may cause important plant diseases that are responsible for major crop losses. Subsequently, the need to understand the molecular mechanisms underlying fungal pathogenicity is of crucial importance. It has been suggested that some microorganisms, including plant growth promoting rhizobacteria (PGPR), manipulate the level of ethylene in plants by cleaving 1-aminocyclopropane-1-carboxylic acid (ACC), an ethylene precursor, into α-ketobutyrate and ammonia using ACC deaminase. In this thesis, it was investigated whether ACC deaminase of Verticillium dahliae, a soil-borne fungal pathogen of many important crops, is involved in pathogenicity of this pathogen. Overexpression of the V. dahliae gene encoding this enzyme, labeled as ACCd, significantly increased virulence in both tomato and eggplant, while deletion of ACCd reduced virulence. Both types of mutant produced more ethylene than the wild type (70V-WT) strain although they significantly differed in ACC content, with overexpressing strains exhibiting lower levels and deletion strains showing higher levels of ACC as compared to the wild type strain. Overexpressing strains were proven to significantly lower the ACC levels in the roots of infected plants while the amount of ACC in the roots of plants infected with deletion mutants increased compared to the wilt type strain. ACC holds a key position in many plant physiological processes with its main role as direct precursor of ethylene. Recent studies have shown that ACC may act as a potential signaling molecule independent from ethylene. To test the hypothesis that ACC acts as a signal for controlling defense, roots of WT and Never Ripe (Nr) tomato plants and Col-0 and etr1-1 Arabidopsis plants were treated with ACC prior to V. dahliae inoculation. Plants pre-treated with ACC displayed less severe symptoms than untreated controls. ACC application on the roots of Col-0 and etr1-1 plants in vitro was also found to trigger root hair formation and induce hormone-dependent defense responses. Collectively, our results suggest a novel role of ACC as a regulator of both plant defense and pathogen virulence.
Keywords: Agricultural productivity; Natural resources; Developing countries